Cancer history and mortality risk in acute myocardial infarction: Insights from the Japan AMI registry - Ayumi Adachi; Kazuma Oyama; Jun Takahashi; Satoshi Honda; Kensaku Nishihira; Sunao Kojima; Misa Takegami; Yasuhide Asaumi; Jun Yamashita; Mike Saji; Kiyoshi Hibi; Yasuhiko Sakata; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: The association between a history of cancer and clinical outcomes in patients with acute myocardial infarction (AMI) remains unclear. This study aimed to analyze the characteristics and clinical outcomes of AMI patients based on their history of cancer in a contemporary cohort undergoing antithrombotic therapy with potent P2Y12 inhibitors. Methods: Consecutive patients with spontaneous onset were enrolled in the Japan AMI Registry (JAMIR), a multi-center, nationwide prospective registry. The outcomes included all-cause death, major bleeding, and composite ischemic events defined as cardiovascular (CV) death, MI, and ischemic stroke. Results: A total of 3,411 AMI patients were enrolled with a median follow-up duration of 358 days. Among those, 292 patients (8.6 %) had a history of cancer. They were older and had lower body mass index. While they had a similar risk of composite ischemic event and major bleeding, they were at higher risk for all-cause mortality than those without (adjHR 1.64 [95 %CI 1.16–2.32], P = 0.005). The risk for non-CV death and death due to cancer were higher in the cancer group (adjHR 2.05 [1.24–3.39], P = 0.005; adjHR 18.16 [6.76–48.97], P < 0.001, respectively). When further stratified by age, the difference in all-cause mortality became pronounced in the group aged < 75 years but not in the group aged ≥ 75 years (adjHR 3.32 [1.88–5.85] and 1.26 [0.81–1.96], respectively; P-interaction = 0.008). Conclusion: The JAMIR demonstrated that a history of cancer was associated with increased mortality in AMI patients aged < 75 years. These results might suggest the need for a multidisciplinary approach to improve their prognosis.